2005
DOI: 10.1097/01.olq.0000180461.30725.f4
|View full text |Cite
|
Sign up to set email alerts
|

Social Marketing Techniques for Public Health Communication: A Review of Syphilis Awareness Campaigns in 8 US Cities

Abstract: Campaigns should address the local epidemic and target audience with culturally appropriate messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…A key method used over the past 10 years to improve knowledge about syphilis has been social marketing including the 'Dogs Are Talking' [71] and the 'Healthy Penis' [72] campaigns in San Francisco, 'Stop the Sores' campaign in Los Angeles [73], 'Got Syph' and 'Don't Be a Sore Loser' in Florida [74]. Some of these campaigns have demonstrated improved awareness of syphilis and how it can be acquired [73,75] and are of particular use in alerting MSM who serosort.…”
Section: Confirmed Diagnosismentioning
confidence: 99%
“…A key method used over the past 10 years to improve knowledge about syphilis has been social marketing including the 'Dogs Are Talking' [71] and the 'Healthy Penis' [72] campaigns in San Francisco, 'Stop the Sores' campaign in Los Angeles [73], 'Got Syph' and 'Don't Be a Sore Loser' in Florida [74]. Some of these campaigns have demonstrated improved awareness of syphilis and how it can be acquired [73,75] and are of particular use in alerting MSM who serosort.…”
Section: Confirmed Diagnosismentioning
confidence: 99%
“…A 1998 article by Lamptey and Price, although not addressing syphilis specifically, offers a good overview regarding the application of social marketing principles to STD campaigns. More recently, in a review of syphilis social marketing efforts in eight U.S. cities, Vega and Roland (2005) report that 71% to 80% of MSM were aware of the campaigns, with 45% to 53% reporting syphilis testing because of the campaigns. Because the authors do not explain the methodology employed by each jurisdiction, however, these results should be viewed with caution.…”
Section: Elements Of Successful Social Marketing Campaignsmentioning
confidence: 99%
“…The research described in this paper is exploratory in nature, limited to a small number of participants and limited to two Australian states; it is likely that different barriers and facilitators will exist in other regions. For example, in a review of formative research conducted for syphilis awareness campaigns in eight US cities, Vega and Roland (2005) concluded that the different messages developed demonstrated the need for culturally appropriate messages to be tailored for each city.…”
Section: Is There a Role For Social Marketing?mentioning
confidence: 98%